Dietary cinnamaldehyde with carvacrol or thymol improves the egg quality and intestinal health independent of gut microbiota in post-peak laying hens - Wang, Yongshuai; Wang, Yilu; Su, Chuanchen; Wang, Leilei; Lv, Xiangyun; Cui, Guangya; Ji, Longxiang; Huang, Yanqun; Zhang, Huaiyong; Chen, Wen (Frontiers in Veterinary Science, 2022)
Essential oils have been proved to exert multiple effects on growth performance, production quality, and health status in poultry nutrition, which dependents on the component and/or dose of essential oils. Diet with optimal combination of essential oils might be able to improve the performance traits and welfare of laying hens. Therefore, this study was carried out to evaluate the effects of dietary essential oils composed of cinnamaldehyde with carvacrol or thymol on performance, egg quality, and intestinal health in post-peak laying hens. A total of 384 50-week-old Hy-line brown laying hens were randomly divided into 3 groups with 8 replicates of 16 birds each: (1) a basal diet (Ctrl), (2) a basal diet with 100 mg/kg essential oils consisted of 4.5% cinnamaldehyde with 13.5% carvacrol (CAR+CIN), and (3) a basal diet contained 100 mg/kg essential oils composed of 4.5% cinnamaldehyde with 13.5% thymol (THY+CIN). The CAR+CIN diet increased the feed consumption during 52 to 55 weeks than the Ctrl and THY+CIN diet. Compared with Ctrl group, the addition of essential oils decreased the dirty egg rate (P = 0.07) in whole trial period. Regarding egg quality, the birds received CAR+CIN and THY+CIN diet increased the eggshell strength (P = 0.099) or Haugh unit (P = 0.03) at 54 weeks, respectively. Supplementation of both CAR+CIN and THY+CIN diet significantly increased the ratio of villus high to crypt depth in duodenum through increasing villus high and decreasing crypt depth, as well as upregulated the mRNA abundances of duodenal occluding and cadherin (P < 0.05). However, the treatment with dietary essential oils did not notably change the proportion of cecal microbiota and bacterial diversity. This study suggests that dietary supplementation of cinnamaldehyde with carvacrol or thymol, the active components of essential oils, could promote egg quality of post-peak laying hens, which might be associate with the improved intestinal development and barrier.